Electrical and optical properties of an organic semiconductor based on polyaniline prepared by emulsion polymerization and fabrication of Ag/polyaniline/n-Si Schottky diode - Yakuphanoğlu, Fahrettin; Basaran, E.; Senkal, B. F.; Sezer, E. (Amer Chemical Soc, 2006)
The electrical, optical, and metal-semiconductor contact properties of the polyaniline prepared by emulsion polymerization have been investigated to obtain an organic semiconductor material. The obtained results suggest that the polyaniline (PANI) studied is an organic semiconductor material with optical band gap (E-g = 2.21 eV) and room electrical conductivity (sigma(25) = 3.12 x 10(-2) S/cm) values. A Schottky diode with configuration Ag/PANI/n-Si was fabricated. The ideality factor and barrier height of Ag/PANI/n-Si diode at room temperature were found to be 4.59 and 0.38 eV, respectively. The obtained diode parameters change with temperature. The Richardson constant A* value for the Ag/PANI/n-Si diode was found to be 3.81 x 10(-4) A/cm(2.)K. The Ag/PANI/n-Si diode is a metal-insulator-semiconductor- type device. The standard deviation, which is a measure of the barrier homogeneity, was found to be 0.14, indicating the presence of interface inhomogeneities. It can be concluded that the polyaniline prepared by emulsion polymerization is an organic semiconductor and Ag/PANI/n-Si configuration shows a Schottky contact.
Keywords: Polymers; Conductivity